The Role Of Customary Institutions In Natural Resource Management In Kailolo, Haruku Island - Marthina Tjoa; Mersiana Sahureka; Arfandy Renyaan (Pattimura University Ambon Maluku Indonesia, 2021)
This study examined the role of sasi institutions in Kailolo negeri with the aim of 1. They are knowing the form of sasi application 2. Assessing the role of sasi institutions in natural resource management in Kailolo Haruku Island Subdistrict, Central Maluku Regency. The method used in this research was qualitative, namely a survey. The study results show that sasi has legal value because it has norms and rules related to ways, habits, behaviour, and customs containing ethics and standards. The role of kewang institutions in Kailolo negeri is perfect because in managing sasi, the community and kewang are together in carrying out their respective functions and responsibilities. There are two sasi in the negeri of Kailolo, namely the Tanjung Moleo sasi and the Forest sasi, which are carried out using an auction system.